Translation as Culture Transfer: Evidence from African Creative Writing - Bandia, Paul (TTR, 1993)
AbstractTranslation as Culture Transfer: Evidence from African Creative Writing — Due to the impact of African oral tradition the language of African creative writing in European languages (French and English) poses specific translation problems. We wish to illustrate the various processes and techniques used to cope with these translation problems. The different translation techniques discussed will throw some light on well-known concepts in translation theory such as Newmark's semantic vs communicative translation, House's overt vs covert translation, Diller and Kornelius' primary vs secondary translation and Berman's "traduction ethnocentrique" vs "traduction hypertextuelle." Translation as culture transfer, particularly regarding non-related language cultures, has been discussed by translation theorists such as Mounin, Nida, Lefevere, and Snell-Hornby. Translating African creative works is a double "transposition" process: (1) primary level of translation i.e., the expression of African thought in a European language by an African writer; (2) the "transfer" of African thought from one European language to another by the translator. The primary level of translation results in an African variety of European languages, and the translator's task is to deal with the unique problems posed by this so-called non-standard language. This paper is focussed on the various translation techniques used by translators of African works. These translators show a clear preference for semantic, overt and "literal" translation, in which, in Nida's terms, formal equivalence is given priority over dynamic equivalence. Such an approach is judged by the translators to be the most reliable for an effective representation of African sociocultural and sociolinguistic reality in European languages.